High-performance PA and ABS 5G electromagnetic shielding composite material and preparation method thereof

The composite material addresses the issues of impact strength and electromagnetic shielding in PA/ABS materials by modifying MoS2 with dopamine and epoxy, and optionally incorporating graphene and MoCo bimetallic sulfide, resulting in enhanced mechanical and shielding properties.

CN119192831AActive Publication Date: 2024-12-27ZHEJIANG TONGLI NEW MATERIAL TECH CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411678263.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2024-12-27
Estimated Expiration
2044-11-22

AI Technical Summary

Technical Problem

Conventional PA/ABS composite materials suffer from insufficient impact strength and electromagnetic shielding effect, particularly when MoS2 is added, leading to deterioration in impact resistance.

Method used

A high-performance PA, ABS 5G electromagnetic shielding composite material is prepared by melt extrusion of a PA/ABS alloy material with modified electromagnetic shielding additives, where molybdenum disulfide is modified with dopamine and the PA/ABS alloy material surface is epoxy functionalized, and optionally combined with graphene and a MoCo bimetallic sulfide/graphene composite material, using O2-Ar radio frequency plasma technology to enhance interfacial bonding and electromagnetic shielding.

Benefits of technology

The method significantly improves the impact strength and electromagnetic shielding performance of the composite material by forming a cross-linked network and enhancing electromagnetic wave absorption and dipole polarization.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure GXAADYL6WCNLSKBPF8L67RTRWM1QRH1R3NVQCIW0
    Figure GXAADYL6WCNLSKBPF8L67RTRWM1QRH1R3NVQCIW0
  • Figure WLP4RETYQA72ROTZ81SYDLU3XZBONCQ2SYNO6HM2
    Figure WLP4RETYQA72ROTZ81SYDLU3XZBONCQ2SYNO6HM2
Patent Text Reader

Abstract

The invention relates to the technical field of functionalized PA / ABS composite materials, in particular to a high-performance PA and ABS 5G electromagnetic shielding composite material and a preparation method thereof. The invention relates to a high-performance PA and ABS 5G electromagnetic shielding composite material, which is prepared by melt extrusion of a PA / ABS alloy material and an electromagnetic shielding additive, the electromagnetic shielding additive contains molybdenum disulfide, the electromagnetic shielding additive is modified by dopamine, and the surface of the PA / ABS alloy material is modified by epoxy functionalization. The high-performance PA and ABS 5G electromagnetic shielding composite material disclosed by the invention has excellent electromagnetic shielding effect and impact strength, and can meet electromagnetic shielding requirements in various environments.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of functionalized PA / ABS composite materials, and more specifically, it relates to a high-performance PA, ABS 5G electromagnetic shielding composite material and a preparation method thereof. Background Art

[0002] With the advancement of science and technology and the rapid development of the 5G era, the widespread use of intelligent wireless communication devices has led to increasingly prominent electromagnetic interference problems. For example, EMI generated by lightning, solar flares, and electrostatic discharges can have an adverse effect on power transmission lines and electronic systems. The problem of electromagnetic pollution is becoming increasingly serious, and it can easily interfere with the normal operation of electronic equipment and even affect human health. Therefore, the development of efficient absorbing materials is an important research topic in the fields of aerospace, 5G communications, military and civilian use.

[0003] Transition metal sulfides have excellent chemical stability, unique layered structure and large specific surface area, so they have gradually become a hot spot for electromagnetic shielding materials in recent years. For example, MoS2 has a unique defect structure, large specific surface area and numerous active sites, so it helps to achieve multiple reflections and polarization effects.

[0004] However, with the addition of MoS2, the impact strength of the PA / ABS material used as the matrix will deteriorate significantly. Therefore, there is an urgent need for a PA / ABS 5G electromagnetic shielding composite material that has both excellent impact resistance and electromagnetic shielding effect to adapt to the market. Summary of the invention

[0005] In order to improve the defects of conventional MoS2-PA / ABS composite materials in terms of insufficient impact strength and electromagnetic shielding effect, the present application provides a high-performance PA, ABS 5G electromagnetic shielding composite material and a preparation method thereof.

[0006] In the first aspect, the present application provides a high-performance PA, ABS 5G electromagnetic shielding composite material, which adopts the following technical solution: A high-performance PA, ABS 5G electromagnetic shielding composite material, which is obtained by melt extrusion of PA / ABS alloy material and electromagnetic shielding additives; The electromagnetic shielding additive contains molybdenum disulfide, the electromagnetic shielding additive is modified by dopamine, and the surface of the PA / ABS alloy material is modified by epoxy functionalization.

[0007] Molybdenum disulfide has a large specific surface area and is easy to agglomerate in PA / ABS alloy materials. In addition, the interfacial bonding strength between molybdenum disulfide and PA / ABS alloy materials is insufficient. Therefore, with the addition of MoS2, the impact strength of PA / ABS material as the matrix will deteriorate significantly.

[0008] When the electromagnetic shielding additive is modified with dopamine and the surface of the PA / ABS alloy material is modified with epoxy functionalization, dopamine can undergo oxidative self-polymerization on the surface of the electromagnetic shielding additive to synthesize polydopamine, and polydopamine contains active functional groups such as hydroxyl, amino, and indolyl. The above functional groups can react with the epoxy groups on the surface of the PA / ABS alloy material to form a cross-linked network, thereby effectively improving the interfacial bonding force between the electromagnetic shielding additive and the PA / ABS alloy material, and effectively improving the impact strength of the PA / ABS material.

[0009] Preferably, the electromagnetic shielding additive is a Mo-based metal sulfide / graphene composite material.

[0010] Graphene is a form of carbon. In the field of electromagnetic shielding, due to its two-dimensional structure, large dielectric loss, rich surface area, high carrier mobility, multi-defect structure and low density, when graphene is used in combination with molybdenum disulfide, its electromagnetic shielding effect can be further enhanced.

[0011] Preferably, the electromagnetic shielding additive is a MoCo bimetallic sulfide / graphene composite material.

[0012] Preferably, the method for preparing the electromagnetic shielding material comprises the following steps: A1. Soak the graphene in a hydrochloric acid solution, then heat it at a temperature of 20-30°C for 8-12h, then wash it with deionized water until it is neutral, and dry it at 70-90°C for 20-30h to obtain acidified graphene; Dissolving 2-methylimidazole in deionized water to obtain a 2-methylimidazole solution, dissolving cobalt nitrate in deionized water to obtain a cobalt nitrate solution, and mixing the 2-methylimidazole solution and the cobalt nitrate solution to obtain a mixed solution; The acidified graphene is immersed in the mixed solution for 3-5 hours, then washed with deionized water until neutral, and dried at 70-90° C. for 20-30 hours to obtain a Co metal organic framework / acidified graphene; A2, treating the Co metal organic framework / acidified graphene with O2-Ar radio frequency plasma for 15-25 min with an output power of 200-400 W to obtain a Co metal organic framework / acidified graphene containing oxygen vacancies; A3. Deionized water, sodium molybdate and thioacetamide are mixed, and then the Co metal organic framework / acidified graphene containing oxygen vacancies is immersed therein, and the mixture is sealed and reacted at 140-160° C. for 4-8 hours. After cooling to room temperature, the mixture is filtered, washed and dried, and finally the surface is modified with dopamine to finally obtain a MoCo bimetallic sulfide / graphene composite material.

[0013] The electromagnetic shielding material uses O2-Ar radio frequency plasma technology to treat acidified graphene and form a Co metal organic skeleton rich in oxygen vacancies on the surface, which increases surface defects, is beneficial to the reflection and scattering of electromagnetic waves, thereby broadening the electromagnetic wave absorption performance and compensating for the impedance mismatch and insufficient dielectric loss caused by a single component. At the same time, the introduction of bimetallic sulfide further enhances dipole polarization, giving it excellent electromagnetic wave loss performance.

[0014] Preferably, the method for preparing the electromagnetic shielding material comprises the following steps: A1, soaking 0.1-0.2g of graphene in 80-120ml of 7.8wt% hydrochloric acid solution, then heating at 20-30°C for 8-12h, then washing with deionized water until neutral, and drying at 70-90°C for 20-30h to obtain acidified graphene; Dissolve 0.1-0.2 g of 2-methylimidazole in 80-120 ml of deionized water to obtain a 2-methylimidazole solution, dissolve 0.04-0.06 g of cobalt nitrate in 40-60 ml of deionized water to obtain a cobalt nitrate solution, and mix the 2-methylimidazole solution and the cobalt nitrate solution to obtain a mixed solution; 0.1 g of acidified graphene was immersed in the mixed solution for 3-5 h, then washed with deionized water until neutral, and dried at 70-90° C. for 20-30 h to obtain Co metal organic framework / acidified graphene; A2, treating the Co metal organic framework / acidified graphene with O2-Ar radio frequency plasma for 15-25 min with an output power of 200-400 W to obtain a Co metal organic framework / acidified graphene containing oxygen vacancies; A3, 80-120 ml of deionized water, 0.1-0.2 g of sodium molybdate and 0.1-0.2 g of thioacetamide are mixed, and then the Co metal organic framework containing oxygen vacancies / acidified graphene is immersed therein, and the mixture is sealed and reacted at 140-160° C. for 4-8 h, and after cooling to room temperature, filtered, washed and dried to obtain a crude MoCo bimetallic sulfide / graphene composite material; A4. The crude MoCo bimetallic sulfide / graphene composite material is subjected to dopamine surface modification to finally obtain the MoCo bimetallic sulfide / graphene composite material.

[0015] Preferably, in A4, the specific steps of surface modification of dopamine are: adding 0.4-0.6 g of crude MoCo bimetallic sulfide / graphene composite material to 200-400 ml of deionized water, ultrasonically dispersing in an ice bath for 20-40 min, then adding 1-2 g of dopamine hydrochloride and adjusting the pH value to 8.5 with Tris-HCl buffer, finally stirring and reacting at 50-70° C. for 20-30 h, then centrifuging and washing to remove the lower precipitate, and drying at 70-90° C. for 20-30 h to obtain a MoCo bimetallic sulfide / graphene composite material.

[0016] Preferably, the preparation method of the PA / ABS alloy material comprises the following steps: B1. Mix glucose, sodium pyrophosphate and deionized water, and after the solid is completely dissolved, add ferrous sulfate aqueous solution and mix well to obtain a basic solution; B2. Add polybutadiene latex, deionized water and cumene hydroperoxide to the base solution in sequence, continue the reaction under nitrogen, then add styrene monomer, acrylonitrile monomer, glycidyl methacrylate, cumene hydroperoxide and tert-dodecyl mercaptan, continue the reaction, and after the reaction is completed, perform demulsification, washing, dehydration and drying to obtain a PA / ABS alloy material.

[0017] Preferably, the preparation method of the PA / ABS alloy material comprises the following steps: B1. Mix 0.4-0.6 g glucose, 0.4-0.6 g sodium pyrophosphate and 500-1000 ml deionized water. After the solid is completely dissolved, add 8-12 ml of 1 mg / L ferrous sulfate aqueous solution and mix well to obtain a base solution. B2, add 180-220g polybutadiene latex, 300-500ml deionized water and 0.04-0.06ml cumene hydroperoxide to the base solution in sequence, continue to react at 60-70°C under nitrogen, then add 50-70g styrene monomer, 15-25g acrylonitrile monomer, 1-3g glycidyl methacrylate, 0.5-1.0ml cumene hydroperoxide and 0.2-0.4ml tert-dodecyl mercaptan, continue to react, and after the reaction is completed, perform demulsification, washing, dehydration and drying to obtain a modified ABS alloy material; B3, mixing the modified ABS material and PA6 resin in a mass ratio of (20-30): (70-80), and then extruding to obtain a PA / ABS alloy material; The temperatures of the three zones of the twin-screw extruder from the feeding zone to the nozzle are 220-230°C, 230-240°C, and 230-240°C respectively.

[0018] In the second aspect, the present application provides a method for preparing a high-performance PA, ABS 5G electromagnetic shielding composite material, using the following technical solution: A method for preparing a high-performance PA, ABS 5G electromagnetic shielding composite material, the steps of which are: The PA / ABS alloy material and the electromagnetic shielding additive are mixed in a mass ratio of (5-10):1, and then extruded to obtain the PA / ABS alloy material; The temperatures of the three zones of the twin-screw extruder from the feeding zone to the nozzle are 220-230°C, 230-240°C, and 230-240°C respectively.

[0019] In summary, this application has the following beneficial effects: 1. When the electromagnetic shielding additive is modified with dopamine, and the surface of the PA / ABS alloy material is modified with epoxy functionalization, dopamine can undergo oxidative self-polymerization on the surface of the electromagnetic shielding additive to synthesize polydopamine, and polydopamine contains active functional groups such as hydroxyl, amino, and indolyl. The above functional groups can react with the epoxy groups on the surface of the PA / ABS alloy material to form a cross-linked network, thereby effectively improving the interfacial bonding force between the electromagnetic shielding additive and the PA / ABS alloy material, and effectively improving the impact strength of the PA / ABS material.

[0020] 2. Graphene is a form of carbon. In the field of electromagnetic shielding, due to its two-dimensional structure, large dielectric loss, rich surface area, high carrier migration rate, multi-defect structure and low density, when graphene is used in combination with molybdenum disulfide, its electromagnetic shielding effect can be further enhanced.

[0021] 3. Electromagnetic shielding materials use O2-Ar radio frequency plasma technology to treat acidified graphene and form a Co metal organic skeleton rich in oxygen vacancies on the surface, which increases surface defects, is beneficial to the reflection and scattering of electromagnetic waves, thereby broadening the electromagnetic wave absorption performance and compensating for the impedance mismatch and insufficient dielectric loss caused by a single component. At the same time, the introduction of bimetallic sulfide further enhances dipole polarization, giving it excellent electromagnetic wave loss performance. DETAILED DESCRIPTION

[0022] The present application is further described in detail below in conjunction with Examples 1 to 5 and Comparative Example 1.

[0023] Graphene CAS: 1034343-98-0; Hydrochloric acid CAS: 7647-01-0; 2-Methylimidazole CAS: 693-98-1; Cobalt nitrate CAS: 10141-05-6; Sodium molybdate CAS: 10102-40-6; Thioacetamide CAS: 62-55-5; Dopamine hydrochloride CAS: 62-31-7; Tris-HCl buffer CAS: 1185-53-1; Glucose CAS: 50-99-7 ; Sodium pyrophosphate CAS: 7722-88-5; Ferrous sulfate CAS: 7720-78-7; Polybutadiene latex Henan Wokas Biological CAS: 9003-17-2; Styrene monomer CAS: 100-42-5; Acrylonitrile monomer CAS: 107-13-1; Isopropylbenzene hydroperoxide CAS: 80-15-9; Glycidyl methacrylate CAS: 106-91-2; Tert-dodecyl mercaptan CAS: 25103-58-6.

[0024] A high-performance PA, ABS 5G electromagnetic shielding composite material, which is obtained by mixing a PA / ABS alloy material and an electromagnetic shielding additive in a mass ratio of 9:1, and then extruding and melt-extruding; Among them, the temperatures of the three zones of the twin-screw extruder from the feeding section to the nozzle are: 220°C, 230°C, and 240°C respectively.

[0025] The electromagnetic shielding additive is molybdenum disulfide, the electromagnetic shielding additive is modified by dopamine, and the surface of the PA / ABS alloy material is modified by epoxy functionalization.

[0026] The specific steps of dopamine surface modification are: Add 0.5 g of molybdenum disulfide to 300 ml of deionized water, disperse ultrasonically in an ice bath for 30 minutes, then add 1.5 g of dopamine hydrochloride and adjust the pH value to 8.5 with Tris-HCl buffer, finally stir and react at 60°C for 25 hours, then centrifuge and wash to remove the lower precipitate, and dry at 80°C for 25 hours to obtain an electromagnetic shielding additive.

[0027] The preparation method of PA / ABS alloy material comprises the following steps: B1. Mix 0.5 g glucose, 0.5 g sodium pyrophosphate and 800 ml deionized water. After the solid is completely dissolved, add 10 ml of 1 mg / L ferrous sulfate aqueous solution and mix well to obtain a base solution. B2, 200g polybutadiene latex, 400ml deionized water and 0.05ml cumene hydroperoxide were added to the base solution in sequence, and the reaction was continued at 65°C under nitrogen, and then 60g styrene monomer, 20g acrylonitrile monomer, 2g glycidyl methacrylate, 0.8ml cumene hydroperoxide and 0.3ml tert-dodecyl mercaptan were added, and the reaction was continued. After the reaction was completed, demulsification, washing, dehydration and drying were performed to obtain a modified ABS alloy material; B3, mixing the modified ABS material and PA6 resin at a mass ratio of 25:75, and then extruding to obtain a PA / ABS alloy material; The temperatures of the three zones of the twin-screw extruder from the feeding zone to the nozzle are 220°C, 230°C, and 240°C respectively.

[0028] The difference from Example 1 is that the electromagnetic shielding additive is a molybdenum disulfide / graphene composite material; The preparation method of the electromagnetic shielding additive comprises the following steps: A1, 0.1g of graphene was immersed in 100ml of 7.8wt% hydrochloric acid solution, then heated at 25°C for 10h, then washed with deionized water until neutral, and dried at 80°C for 25h to obtain acidified graphene; A2, 100 ml of deionized water, 0.15 g of sodium molybdate and 0.15 g of thioacetamide were mixed, and then the acidified graphene was immersed therein, and the mixture was sealed and reacted at 150 ° C for 6 h. After cooling to room temperature, the mixture was filtered, washed and dried to obtain a molybdenum disulfide / graphene composite material; A4. The molybdenum disulfide / graphene composite material is subjected to dopamine surface modification. The specific steps of dopamine surface modification are as follows: 0.5 g of molybdenum disulfide / graphene composite material was added to 300 ml of deionized water, ultrasonically dispersed in an ice bath for 30 min, and then 1.5 g of dopamine hydrochloride was added and the pH value was adjusted to 8.5 with Tris-HCl buffer. Finally, the reaction was stirred at 60 ° C for 24 h, and then the lower layer of precipitate was removed by centrifugation and washed with water, and dried at 80 ° C for 24 h to obtain an electromagnetic shielding additive.

[0029] The difference from Example 1 is that the electromagnetic shielding additive is a MoCo bimetallic sulfide / graphene composite material; The preparation method of the electromagnetic shielding additive comprises the following steps: A1, 0.1g of graphene was immersed in 100ml of 7.8wt% hydrochloric acid solution, then heated at 25°C for 10h, then washed with deionized water until neutral, and dried at 80°C for 25h to obtain acidified graphene; Dissolve 0.1 g of 2-methylimidazole in 100 ml of deionized water to obtain a 2-methylimidazole solution, dissolve 0.05 g of cobalt nitrate in 50 ml of deionized water to obtain a cobalt nitrate solution, and mix the 2-methylimidazole solution and the cobalt nitrate solution to obtain a mixed solution; 0.1 g of acidified graphene was immersed in the mixed solution for 4 h, then washed with deionized water until neutral, and dried at 80 °C for 24 h to obtain Co metal organic framework / acidified graphene; A2, treating the Co metal organic framework / acidified graphene with O2-Ar radio frequency plasma for 20 min with an output power of 300 W to obtain a Co metal organic framework / acidified graphene containing oxygen vacancies; A3, 100 ml of deionized water, 0.15 g of sodium molybdate and 0.15 g of thioacetamide were mixed, and then the Co metal organic framework containing oxygen vacancies / acidified graphene was immersed therein, and the mixture was sealed and reacted at 150° C. for 6 h. After cooling to room temperature, the mixture was filtered, washed and dried to obtain a crude MoCo bimetallic sulfide / graphene composite material; A4. The crude MoCo bimetallic sulfide / graphene composite material is subjected to dopamine surface modification. The specific steps of the dopamine surface modification are as follows: 0.5 g of crude MoCo bimetallic sulfide / graphene composite material was added to 300 ml of deionized water, ultrasonically dispersed in an ice bath for 30 min, and then 1.5 g of dopamine hydrochloride was added and the pH value was adjusted to 8.5 with Tris-HCl buffer. Finally, the reaction was stirred at 60 °C for 24 h, and then the lower precipitate was removed by centrifugation and washed with water, and dried at 80 °C for 24 h to obtain an electromagnetic shielding additive.

[0030] Example 4-Example 5 The difference from Example 3 is that the added amounts of graphene, cobalt nitrate and sodium molybdate are different, as shown in Table 1.

[0031] Table 1 The addition amount of graphene, cobalt nitrate and sodium molybdate in Examples 3 to 5 Comparative Example 1 The difference from Example 1 is that the electromagnetic shielding additive is no longer modified with dopamine, that is, molybdenum disulfide is directly added, and the surface of the PA / ABS alloy material is no longer modified with epoxy functionalization, that is, glycidyl methacrylate is no longer added.

[0032] 1. Electromagnetic shielding effect test The test used a vector network analyzer, fortunately Agilent N5244A, the test method was coaxial transmission reflection method, the test model was NRW two-port network model, the test frequency was 2-18GHz, three samples were taken from Examples 1 to 5 and Comparative Example 1, the samples were annular in structure, with an inner diameter of 3mm, an outer diameter of 7mm, and a thickness of 5mm, the maximum reflection loss was tested.

[0033] 2. Impact strength test Three samples were taken from each of Examples 1 to 5 and Comparative Example 1, and then the impact strength of the samples was tested according to ISO 180:2019 “Determination of Izod Impact Strength of Plastics” and the average value was taken.

[0034] The test data are shown in Table 2.

[0035] Table 2 Test data table of Example 1 to Example 5 and Comparative Example 1 With reference to Examples 1 to 5 and Comparative Example 1, it can be seen that the impact strengths of Examples 1 to 5 are significantly increased compared with Comparative Example 1, which indicates that dopamine modification of electromagnetic shielding additives and epoxy modification of PA / ABS alloy materials can effectively improve the mechanical properties of composite materials.

[0036] The reason is that when the electromagnetic shielding additive is modified with dopamine and the surface of the PA / ABS alloy material is modified with epoxy functionalization, dopamine can undergo oxidative self-polymerization on the surface of the electromagnetic shielding additive to synthesize polydopamine, and polydopamine contains active functional groups such as hydroxyl, amino, and indolyl. The above functional groups can react with the epoxy groups on the surface of the PA / ABS alloy material to form a cross-linked network, thereby effectively improving the interfacial bonding force between the electromagnetic shielding additive and the PA / ABS alloy material, and effectively improving the impact strength of the PA / ABS material.

[0037] With reference to Comparative Example 1, the maximum reflection loss of Example 1 is slightly improved, which shows that the electromagnetic shielding effect of the composite material can be slightly improved by modifying the electromagnetic shielding additive with dopamine and modifying the PA / ABS alloy material with epoxy. The reason may be that epoxy modification and dopamine modification can effectively improve the compatibility of the electromagnetic shielding additive with the PA / ABS alloy material, and indirectly improve the electromagnetic shielding effect of the composite material.

[0038] With reference to Example 1-Example 2 and in combination with Table 2, it can be seen that, relative to Example 1, the maximum reflection loss of Example 2 is further increased, which indicates that the addition of graphene can further enhance the electromagnetic shielding effect of the composite material.

[0039] The reason is that graphene is a form of carbon element. In the field of electromagnetic shielding, due to its two-dimensional structure, large dielectric loss, rich surface area, high carrier migration rate, multi-defect structure and low density, when graphene is used in combination with molybdenum disulfide, its electromagnetic shielding effect can be further enhanced.

[0040] Referring to Example 2-Example 3 and combining with Table 2, it can be seen that compared with Example 2, the maximum reflection loss of Example 3 is significantly increased, which shows that replacing molybdenum disulfide with bimetallic sulfide can significantly improve the electromagnetic shielding effect of the composite material.

[0041] The reason is that the electromagnetic shielding material uses O2-Ar radio frequency plasma technology to treat acidified graphene and form a Co metal organic skeleton rich in oxygen vacancies on the surface, which increases surface defects and is beneficial to the reflection and scattering of electromagnetic waves, thereby broadening the electromagnetic wave absorption performance and compensating for the impedance mismatch and insufficient dielectric loss caused by a single component. At the same time, the introduction of bimetallic sulfide further enhances the dipole polarization, giving it excellent electromagnetic wave loss performance.

[0042] With reference to Examples 3 to 5 and in combination with Table 2, it can be seen that, relative to Example 3, the maximum reflection losses of Examples 4 to 5 are slightly reduced, which indicates that when graphene, cobalt nitrate and sodium molybdate are added in the amounts of Example 3, the prepared composite material will have a better electromagnetic shielding effect.

[0043] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed. However, as long as it is within the scope of the claims of the present application, it shall be protected by the patent law.

Claims

1. A high-performance PA, ABS 5G electromagnetic shielding composite material, characterized in that: It is obtained by melt extrusion of PA / ABS alloy material and electromagnetic shielding additives; The electromagnetic shielding additive contains molybdenum disulfide, the electromagnetic shielding additive is modified by dopamine, and the surface of the PA / ABS alloy material is modified by epoxy functionalization.

2. The high-performance PA, ABS 5G electromagnetic shielding composite material according to claim 1, characterized in that: The electromagnetic shielding additive is a Mo-based metal sulfide / graphene composite material.

3. The high-performance PA, ABS 5G electromagnetic shielding composite material according to claim 2, characterized in that: The electromagnetic shielding additive is a MoCo bimetallic sulfide / graphene composite material.

4. The high-performance PA, ABS 5G electromagnetic shielding composite material according to claim 3, characterized in that: The preparation method of the electromagnetic shielding material comprises the following steps: A1. Soak the graphene in a hydrochloric acid solution, then heat it at a temperature of 20-30°C for 8-12h, then wash it with deionized water until it is neutral, and dry it at 70-90°C for 20-30h to obtain acidified graphene; Dissolving 2-methylimidazole in deionized water to obtain a 2-methylimidazole solution, dissolving cobalt nitrate in deionized water to obtain a cobalt nitrate solution, and mixing the 2-methylimidazole solution and the cobalt nitrate solution to obtain a mixed solution; The acidified graphene is immersed in the mixed solution for 3-5 hours, then washed with deionized water until neutral, and dried at 70-90° C. for 20-30 hours to obtain a Co metal organic framework / acidified graphene; A2, treating the Co metal organic framework / acidified graphene with O2-Ar radio frequency plasma for 15-25 min with an output power of 200-400 W to obtain a Co metal organic framework / acidified graphene containing oxygen vacancies; A3. Deionized water, sodium molybdate and thioacetamide are mixed, and then the Co metal organic framework / acidified graphene containing oxygen vacancies is immersed therein, and the mixture is sealed and reacted at 140-160° C. for 4-8 hours. After cooling to room temperature, the mixture is filtered, washed and dried, and finally the surface is modified with dopamine to finally obtain a MoCo bimetallic sulfide / graphene composite material.

5. The high-performance PA, ABS 5G electromagnetic shielding composite material according to claim 4, characterized in that: The preparation method of the electromagnetic shielding material comprises the following steps: A1, soaking 0.1-0.2g of graphene in 80-120ml of 7.8wt% hydrochloric acid solution, then heating at 20-30°C for 8-12h, then washing with deionized water until neutral, and drying at 70-90°C for 20-30h to obtain acidified graphene; Dissolve 0.1-0.2 g of 2-methylimidazole in 80-120 ml of deionized water to obtain a 2-methylimidazole solution, dissolve 0.04-0.06 g of cobalt nitrate in 40-60 ml of deionized water to obtain a cobalt nitrate solution, and mix the 2-methylimidazole solution and the cobalt nitrate solution to obtain a mixed solution; 0.1 g of acidified graphene was immersed in the mixed solution for 3-5 h, then washed with deionized water until neutral, and dried at 70-90° C. for 20-30 h to obtain Co metal organic framework / acidified graphene; A2, treating the Co metal organic framework / acidified graphene with O2-Ar radio frequency plasma for 15-25 min with an output power of 200-400 W to obtain a Co metal organic framework / acidified graphene containing oxygen vacancies; A3, 80-120 ml of deionized water, 0.1-0.2 g of sodium molybdate and 0.1-0.2 g of thioacetamide are mixed, and then the Co metal organic framework containing oxygen vacancies / acidified graphene is immersed therein, and the mixture is sealed and reacted at 140-160° C. for 4-8 h, and after cooling to room temperature, filtered, washed and dried to obtain a crude MoCo bimetallic sulfide / graphene composite material; A4. The crude MoCo bimetallic sulfide / graphene composite material is subjected to dopamine surface modification to finally obtain the MoCo bimetallic sulfide / graphene composite material.

6. The high-performance PA, ABS 5G electromagnetic shielding composite material according to claim 5, characterized in that: In A4, the specific steps of dopamine surface modification are: 0.4-0.6 g of crude MoCo bimetallic sulfide / graphene composite material is added to 200-400 ml of deionized water, ultrasonically dispersed in an ice bath for 20-40 min, and then 1-2 g of dopamine hydrochloride is added and the pH value is adjusted to 8.5 with Tris-HCl buffer. Finally, the reaction is stirred at 50-70° C. for 20-30 h, and then the lower precipitate is removed by centrifugal washing and dried at 70-90° C. for 20-30 h to obtain a MoCo bimetallic sulfide / graphene composite material.

7. The high-performance PA, ABS 5G electromagnetic shielding composite material according to claim 1, characterized in that: The preparation method of the PA / ABS alloy material comprises the following steps: B1. Mix glucose, sodium pyrophosphate and deionized water, and after the solid is completely dissolved, add ferrous sulfate aqueous solution and mix well to obtain a basic solution; B2. Add polybutadiene latex, deionized water and cumene hydroperoxide to the base solution in sequence, continue the reaction under nitrogen, then add styrene monomer, acrylonitrile monomer, glycidyl methacrylate, cumene hydroperoxide and tert-dodecyl mercaptan, continue the reaction, and after the reaction is completed, perform demulsification, washing, dehydration and drying to obtain a PA / ABS alloy material.

8. The high-performance PA, ABS 5G electromagnetic shielding composite material according to claim 7, characterized in that: The preparation method of the PA / ABS alloy material comprises the following steps: B1. Mix 0.4-0.6 g glucose, 0.4-0.6 g sodium pyrophosphate and 500-1000 ml deionized water. After the solid is completely dissolved, add 8-12 ml of 1 mg / L ferrous sulfate aqueous solution and mix well to obtain a base solution. B2, add 180-220g polybutadiene latex, 300-500ml deionized water and 0.04-0.06ml cumene hydroperoxide to the base solution in sequence, continue to react at 60-70°C under nitrogen, then add 50-70g styrene monomer, 15-25g acrylonitrile monomer, 1-3g glycidyl methacrylate, 0.5-1.0ml cumene hydroperoxide and 0.2-0.4ml tert-dodecyl mercaptan, continue to react, and after the reaction is completed, perform demulsification, washing, dehydration and drying to obtain a modified ABS alloy material; B3, mixing the modified ABS material and PA6 resin in a mass ratio of (20-30): (70-80), and then extruding to obtain a PA / ABS alloy material; The temperatures of the three zones of the twin-screw extruder from the feeding zone to the nozzle are 220-230°C, 230-240°C, and 230-240°C respectively.

9. A method for preparing the high-performance PA, ABS 5G electromagnetic shielding composite material according to any one of claims 1 to 8, characterized in that: The steps are: The PA / ABS alloy material and the electromagnetic shielding additive are mixed in a mass ratio of (5-10):1, and then extruded to obtain the PA / ABS alloy material; The temperatures of the three zones of the twin-screw extruder from the feeding zone to the nozzle are 220-230°C, 230-240°C, and 230-240°C respectively.

Citation Information

Patent Citations

  • Magnetoelectric coupling type electromagnetic shielding film and preparation method and application

    CN113831599A

  • Composite shielding material and preparation method thereof

    CN116355586A

  • Multi-interface graphene-based electromagnetic shielding composite material and preparation method thereof

    CN116887592A

  • Light-weight porous mxene-based composite thin film electromagnetic shielding material and preparation method therefor

    WO2022242256A1

  • High-entropy alloy sulfide / two-dimensional NANO composite material, preparation method therefor, and application thereof

    WO2023197954A1